2016
DOI: 10.1016/j.bbrep.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microwave radiation of cytochrome CYP102 A1 solution during the enzyme reaction

Abstract: Microwave radiation at 3.4–4.2 GHz frequency of the cytochrome P450 CYP102 A1 (BM3) solution was registered during the lauric acid hydroxylation reaction. The microwave radiation generation was shown to occur following the addition of electron donor NADPH to a system containing an enzyme and a substrate. The radiation occurs for the enzyme solutions with enzyme concentrations of 10−8 and 10−9 М. The microwave radiation effect elicited by the aqueous enzyme solution was observed for the first time. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…An RTM-01 RES broadband radiometer with the operating range from 3.4 to 4.2 GHz was used as a microwave radiation detector. During the measurements of the brightness temperature of the solution, a buggy-whip antenna of the detector was entirely immersed into the sample solution, similar to [2]. As noted in Introduction, the radiometer measures the object's brightness temperature.…”
Section: Analytical Measurementsmentioning
confidence: 99%
See 4 more Smart Citations
“…An RTM-01 RES broadband radiometer with the operating range from 3.4 to 4.2 GHz was used as a microwave radiation detector. During the measurements of the brightness temperature of the solution, a buggy-whip antenna of the detector was entirely immersed into the sample solution, similar to [2]. As noted in Introduction, the radiometer measures the object's brightness temperature.…”
Section: Analytical Measurementsmentioning
confidence: 99%
“…Radiation from enzyme systems can be observed in other spectral ranges as well. In this way, previously it was demonstrated that the functioning of the CYP102A1 enzyme system in a narrow concentration range (from 10 −9 V to 10 −8 V) is accompanied by a microwave radiation in the form of pulse trains at 3.4 to 4.2 GHz frequency [2]. In [2], a radiothermometry method was employed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations